Illustrated Key to the Genera of Free-Living Marine Nematodes in the Superfamily Chromadoroides Exclusive of the Chromadoridae - Armen C. Tarjan; Edwin J. Keppner (EDIS, 2003)
This is an illustrated key to 55 genera of free-living marine nematodes of the superfamily Chromadoroidea, exclusive of the Chromadoridae, (Nematoda: Chromadorida: Chromadorina). Illustrations are almost all limited to the heads and caudal regions of the included genera. Specific anatomical features are designated to facilitate use of the key. This document is EENY-082, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 1999.